Maternal Posyandu Participation and Toddler Nutritional Status in Gribig Village: Keaktifan Ibu Posyandu dan Status Gizi Balita di Desa Gribig - Retno setiyowati; Umi Faridah; Rusnoto Rusnoto (Academia Open, 2026)
General Background: Toddler nutritional status reflects health conditions and adequate nutrient intake supporting optimal child growth and development. Specific Background: Maternal participation in Posyandu, parenting patterns, and feeding practices are factors related to child nutrition monitoring. Knowledge Gap: Many studies discuss these determinants separately, while integrated evidence in rural community settings remains limited. Aims: This study aimed to analyze the relationship between maternal activeness in Posyandu, parenting patterns, and feeding practices with toddler nutritional status in Gribig Village. Results: A quantitative cross-sectional study was conducted involving 59 mothers with toddlers aged 0–59 months. The results showed a significant relationship between maternal Posyandu participation and toddler nutritional status (p=0.0001). Parenting patterns and feeding practices showed tendencies toward better nutritional conditions but were not statistically significant (p=0.7 and p=0.8). Most toddlers had normal nutritional status (69.5%), and democratic parenting was the most common pattern. Novelty: This study integrates maternal participation, parenting patterns, and feeding practices using community-based Posyandu data. Implications: Strengthening maternal participation and community nutrition education can support routine monitoring and early detection of toddler nutritional problems. Highlights • Maternal participation associated with toddler nutrition monitoring• Majority of toddlers categorized with normal nutrition• Democratic caregiving approach most commonly practiced Keywords Maternal Posyandu Participation; Parenting Patterns; Feeding Practices; Toddler Nutritional Status; Community Health Monitoring